2013
DOI: 10.1021/es304056n
|View full text |Cite
|
Sign up to set email alerts
|

Metal Mobilization by Iron- and Sulfur-Oxidizing Bacteria in a Multiple Extreme Mine Tailings in the Atacama Desert, Chile

Abstract: The marine shore sulfidic mine tailings dump at the Chañaral Bay in the Atacama Desert, northern Chile, is characterized by extreme acidity, high salinity, and high heavy metals concentrations. Due to pyrite oxidation, metals (especially copper) are mobilized under acidic conditions and transported toward the tailings surface and precipitate as secondary minerals (Dold, Environ. Sci. Technol. 2006, 40, 752-758.). Depth profiles of total cell counts in this almost organic-carbon free multiple extreme environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…36 H 2 S could be converted to sulfuric acid (H 2 SO 4 ) by SOB, resulting in serious iron corrosion. 37 In the present study, SRB and SOB were mainly found in the inner layer (under anaerobic conditions), and the corrosion rate of cast iron coupons at Stage II was positively correlated with SRB (R ¼ 0.74) and SOB (R ¼ 0.97). This result might indicate that growth and interaction of SRB and SOB were mainly associated with anaerobic iron corrosion.…”
Section: Corrosion Rate and Bacterial Communitiessupporting
confidence: 54%
“…36 H 2 S could be converted to sulfuric acid (H 2 SO 4 ) by SOB, resulting in serious iron corrosion. 37 In the present study, SRB and SOB were mainly found in the inner layer (under anaerobic conditions), and the corrosion rate of cast iron coupons at Stage II was positively correlated with SRB (R ¼ 0.74) and SOB (R ¼ 0.97). This result might indicate that growth and interaction of SRB and SOB were mainly associated with anaerobic iron corrosion.…”
Section: Corrosion Rate and Bacterial Communitiessupporting
confidence: 54%
“…Because of their biological and geochemical simplicity and the steep environmental gradients associated with different oxidation stages, the extreme tailing environments are ideal targets for the study of local microbial diversity and how communities respond to environmental changes. The microbial community diversity in mine tailings has recently been investigated by comparative 16S rRNA sequencing (12)(13)(14)(15)(16). While these studies have significantly expanded our knowledge of the biodiversity of extreme tailing environments (including the detection of less-well-known or novel taxa), systematic exploration of the driving factors in local community composition and how microbial populations interact with changing environmental conditions has thus far been impossible.…”
mentioning
confidence: 99%
“…According to the literature these microorganisms often occur in dumps of mine waste rockandtailingsfrom sulfide ore processingplants. Acidophiliciron(II)-andsulfuroxidizing bacteria are responsible for the release of sulfuric acid which are able to promote the release of metals from the tailing dumps [21].Heterotrophic bacteria were represented by Bacillussp and Pseudomonassp which are among the bacteria species must likely to degrade the organic matter to form organic acids; these species were found at all the sampling sites. …”
Section: Microorganisms In the Tailing Dumpsmentioning
confidence: 99%